Metadata functional requirements for genomic data practice and curation - Hong Huang; Jian Qin (Information Research: An International Electronic Journal)
Introduction. The rapid accumulation of genomic data and their widespread reuse in clinical and scientific practice demands more effective description and organization of genomic information, which poses new challenges in developing metadata schemas. Based on a previously developed taxonomy of metadata requirements, this paper reports the results from a survey that addresses these new challenges.